Persistent zooplankton bioregions reflect long-term consistency of community composition and oceanographic drivers in the NE Pacific. (August 2022) - Pata, Patrick R.; Galbraith, Moira; Young, Kelly; Margolin, Andrew R.; Perry, R. Ian; Hunt, Brian P.V.
Graphical abstract: Highlights: Cluster analysis of 20 years of zooplankton data identified 4 persistent bioregions. Bioregions differed in zooplankton concentration, diversity, and composition. Concordance and indicator value analysis defined species association groups. Oceanography and zooplankton ecology are summarized along the cross-shelf gradient. Abstract: Understanding oceanic ecological processes requires identifying biogeographic regions but incorporating the partitioning of planktonic communities, particularly zooplankton, has been limited and difficult. We conducted a data-driven biogeographic regionalization of zooplankton abundance using net data collected during April to October from 1995 to 2014 in the British Columbia, Canada, coastal ocean and adjacent offshore waters. After curating the data and removing rare taxa, a total of 3, 721 samples and 160 species were analyzed. K-means cluster analysis of log-chord transformed zooplankton abundances was used to identify four distinct bioregions: Offshore, Deep Shelf, Nearshore, and Deep Fjord. We combined concordance and indicator value analyses to categorize the zooplankton into species association groups. Five main groups representing subarctic, subtropical, widespread shelf, neritic, and fjord specific zooplankton were indicative of specific bioregions but had distributions extending beyond their core bioregion. The spatial coherence of the bioregions and the relative contributions of the association groups to the composition of the bioregions were persistent throughout the 20-year period. The bioregions significantly differed in zooplankton abundance, biomass, and diversity and the community composition varied along the cross-shelf gradient. Variance partitioning demonstrated that the bioregionalization can be mostly explained by the differences in bottom depth, water properties, and phytoplankton concentrations. The cross-shelf differentiation of zooplankton communities was similar to other regionalization studies conducted globally, suggesting the potential for a unified framework of structuring processes and emergent community properties in the epipelagic coastal ocean.